Poster 239: Limb Malalignment Fails to Influence Clinical Outcomes of Meniscal Repair. Issue 7 (30th July 2022) - Palumbo, Reid; Cavendish, Parker; Milliron, Eric; Milliron, Eric; Dibartola, Alex; Duerr, Robert; Magnussen, Robert; Kaeding, Christopher; Flanigan, David; Swinehart, Steven
Objectives: Lower limb malalignment causes differences in tibiofemoral contact pressures and may influence outcomes following meniscal repair. Our objective was to evaluate clinical outcomes of meniscal repair in malaligned knees to determine if limb malalignment portends an inferior outcome. We hypothesized that medial meniscus repairs performed in varus knees and lateral meniscus repairs performed in valgus knees would result in poorer patient-reported outcomes when compared to a neutrally aligned knee. Methods: Patients who underwent meniscal repair at a single institution between 2006 and 2018 were identified by retrospective chart review. Patients between the ages of 18 and 65 with full-length weight bearing lower limb radiographs were included. Patients with varus alignment (> 3 degrees) and a medial meniscus repair, or valgus alignment (>3 degrees) and a lateral meniscus repair were considered "at-risk". Outcomes were assessed through identification of additional surgery on the index meniscus and patient-reported outcome measures (PROMs): Knee Injury and Osteoarthritis Outcome Score (KOOS), Marx activity score, and International Knee Documentation Committee subjective score (IKDC). Failure rates and PROMs were compared between the at-risk and not at risk groups. Results: A total of 58 patients were included with a mean follow-up of 1.6 years. A total of 12 patients were classified as "at-risk". Repeat surgery on the index meniscus was performed in 1 of 12 "at risk" patients (8.3%) and 7 of 46 (15.2%) in the "not at risk" group (p = 1.00). There were no significant differences between the two groups in KOOS subscales: pain (82.8 vs 85.6, p = 0.55), symptoms (78.2 vs 80.8, p = 0.64), ADLs (88.4 vs 92.9, p = 0.27), Sport/Rec Function (63.8 vs 69.2, p = 0.57), or QOL (58.9 vs 62.3, p = 0.69). There was also no difference in IKDC score (66.9 vs 72.5, p = 0.41) or Marx score (4.2 vs 5.0, p = 0.63) between the two groups. Conclusions: Pre-operative knee malalignment does not appear to negatively influence clinical outcomes of meniscal repair when compared to normal knee alignment. Table 1. Patient-Reported Outcome Scores